# The vertices of ΔXYZ are X(−3, −6), Y(21, −6), and Z(21, 4). What is the perimeter of the triangle?

QUESTION POSTED AT 05/12/2019 - 06:58 AM ## Related questions

### Dpoiski2 Find the perimeter of a rectangle with l = 0.85 m and w = 0.4 m. A. 1.25 m B. 2.5 m C. 0.34 m D. 0.68 m Unsubscribe

For this question the answer is 2.5m (B)
You find this by: L=0.85m
W=0.4m

A rectangle had 4 sides (2 lengths and 2 widths)
So...
To find 1 length and 1 Width you do 0.85+0.4=1.25m
Now you want to find the other 2 sides (L and W)
You can do: the same method and add it to 1.25m OR...
You can do (I prefer this one): (0.85+0.4)x2=?
This is the same as 0.85+0.4=1.25
1.25x2=2.5m

ANSWERED AT 18/01/2020 - 07:41 AM

QUESTION POSTED AT 18/01/2020 - 07:41 AM

### Which represents a quadratic function? f(x) = 2x3 + 2x2 – 4 f(x) = –7x2 – x + 2 f(x) = –3x + 2 f(x) = 0x2 + 3x – 3

Answer is b (f(x)=-7x^2-x+2) thats the only one that follows standard form

ANSWERED AT 18/01/2020 - 07:41 AM

QUESTION POSTED AT 18/01/2020 - 07:41 AM

### Omar grouped the terms and factored the GCF out of the groups of the polynomial 3x3 – 15x2 – 4x + 20. His work is shown. Step 1: (3x3 – 15x2) + (–4x + 20) Step 2: 3x2(x – 5) + 4(–x + 5) Omar noticed that he does not have a common factor. Which accurately describes what Omar should do next? A: Omar should realize that his work shows that the polynomial is prime. B: Omar should go back and regroup the terms in Step 1 as (3x3 – 15x2) – (4x + 20). C: In Step 2, Omar should factor only out of the first expression. D: Omar should factor out a negative from one of the groups so the binomials will be the same.

Omar should factor out a negative from one of the groups so the binomials will be the same.

ANSWERED AT 18/01/2020 - 07:40 AM

QUESTION POSTED AT 18/01/2020 - 07:40 AM

### N Panama City in January, high tide was at midnight. The water level at high tide was 9 feet and 1 foot at low tide. Assuming the next high tide is exactly 12 hours later and that the height of the water can be modeled by a cosine curve, find an equation for water level in January for Panama City as a function of time (t). f(t) = 4 cospi over 2t + 5 f(t) = 5 cospi over 2t + 4 f(t) = 5 cospi over 6t + 4 f(t) = 4 cospi over 6t + 5

The period of this function ( cos (bx) ):
T = b= Maximum  tide : 9 feet (for cos value 1) f(t)=4*1 + 5 = 9
Minimum tide: 1 feet ( for cos value -1) f(t) = 4*(-1) + 5 =1
Answer: D) f(t)= 4 cos (π/6 t) +5

ANSWERED AT 18/01/2020 - 07:40 AM

QUESTION POSTED AT 18/01/2020 - 07:40 AM

### Which functions have an axis of symmetry of x = –2? Check all that apply. f(x) = x2 + 4x + 3 f(x) = x2 – 4x – 5 f(x) = x2 + 6x + 2 f(x) = –2x2 – 8x + 1 f(x) = –2x2 + 8x – 2

Answer : Given: axis of symmetry of x = –2

To find axis of symmetry we use formula We check which equation has axis of symmetry x= -2

(1) a=1 , b=4 so axis of symmetry (2) a=1 , b=-4 so axis of symmetry (3) a=1 , b=6 so axis of symmetry (4) a=-2 , b=-8 so axis of symmetry (5) a=-2 , b=8 so axis of symmetry So and has axis of symmetry x=-2

ANSWERED AT 18/01/2020 - 07:37 AM

QUESTION POSTED AT 18/01/2020 - 07:37 AM

### Find an equation that models a hyperbolic lens with a = 12 inches and foci that are 26 inches apart. Assume that the center of the hyperbola is the origin and the transverse axis is vertical.

The general form for a hyperbola with the center at the origin and a vertical transverse axis is:
y2/a2 - x2/b2 = 1

From the given:
a = 12

To get b, we use the given distance between the foci.Since it's 26,
c = 26/2 = 13

Using this defintion:
c2 = a2 + b2
b = sqrt(c2 - a2) = sqrt (13^2 - 12^2) = 5

The equation therefore is:
y2/13^2 - x2/5^2 = 1
or
y2/169 - x2/25 = 1

ANSWERED AT 18/01/2020 - 07:36 AM

QUESTION POSTED AT 18/01/2020 - 07:36 AM

### Tara is using matrix multiplication to find image points of a translation. She is translating the image 2 units left and 4 units up. Which should be her first matrix?

Assuming that this is just on a 2-D coordinate plane, we must convert the expressions on to a 3-D plane since translation cannot be done on a 2-D plane. This is done by adding a dummy coordinate that does not change. Let us use "1" for this case.

Matrix:
| 0 0 -2 |(x) = (x - 2)
| 0 0 4  |(y) = (y + 4)
| 0 0 1  |(1) = 1

ANSWERED AT 18/01/2020 - 07:35 AM

QUESTION POSTED AT 18/01/2020 - 07:35 AM

### Based only on the information given in the diagram, which congruence theorems or postulates could be given as reasons why triangle hel is congruent to triangle pme

Hi :) Firstly we look at the side that is actually the same. How many sides are there that are the same? Next, we note the number of angles that are the same.

ANSWERED AT 18/01/2020 - 07:30 AM

QUESTION POSTED AT 18/01/2020 - 07:30 AM

### Which shows three ordered pairs that are all solutions of the equation y = x + 8? A. (0, 8), (1, 7), and (2, 9) B. (1, 8), (2, 16), and (3, 24) C. (1, 9), (3, 11), and (5, 13) D. (8, 0), (9, 1), and (10, 2)

ANSWERED AT 18/01/2020 - 07:30 AM

QUESTION POSTED AT 18/01/2020 - 07:30 AM

### Point A is located at (4, 0) and is reflected in the x-axis. What are the coordinates of point A'? (0, 4) (0, -4) (-4, 0) (4, 0)

(4,0) I don't know how to explain.

Step-by-step explanation:

ANSWERED AT 18/01/2020 - 07:29 AM

QUESTION POSTED AT 18/01/2020 - 07:29 AM

### The first steps in writing f(x) = 3x2 – 24x + 10 in vertex form are shown. f(x) = 3(x2 – 8x) + 10 (-8/2)^2 = 16 What is the function written in vertex form? A.f(x) = 3(x + 4)2 – 6 B.f(x) = 3(x + 4)2 – 38 C.f(x) = 3(x – 4)2 – 6 D.f(x) = 3(x – 4)2 – 38

Following the steps already shown to transform the given function into the vertex form, we have:

f(x) = 3(x2 - 8x + 16) + 10 - 3(16)
f(x) = 3(x - 4)(x - 4) + 10 - 48
f(x) = 3(x - 4)2 - 38

Therefore, the function written in vertex form is:
D.f(x) = 3(x – 4)2 – 38

ANSWERED AT 18/01/2020 - 07:28 AM

QUESTION POSTED AT 18/01/2020 - 07:28 AM

### When f(x)=4, what is the value of x? 0 2 3 4

3

Step-by-step explanation:

on edguinity just look at the arrow

ANSWERED AT 18/01/2020 - 07:28 AM

QUESTION POSTED AT 18/01/2020 - 07:28 AM

### A bag has 5 red marbles, 6 blue marbles and 4 black marbles. What is the probability of picking a red marble, replacing it, and then picking another red marble? Working;
The probability of picking a red is The probability remains the same for the second picking since there is replacement;
A red followed by a red is; ANSWERED AT 18/01/2020 - 07:24 AM

QUESTION POSTED AT 18/01/2020 - 07:24 AM

### Scientists studied a deer population for 10 years. They generated the function f(x) = 248(1.15)^x to approximate the number of deer in the population x years after beginning the study. About how many deer are in the population 3 years after beginning the study? 251 377 856 1,003

f(x) = 248(1.15)^x

This is a simple case of substitution. We plug in the value of 3 to the function:
f(3) = 248 (1.15)^3

The radical term can be solved first before multiplying with 248 to get the result or a basic scientific calculator can be used to solve this:
f(3) = 377.18 (round off to 377)

Therefore, the answer is the second option:
377

ANSWERED AT 18/01/2020 - 07:23 AM

QUESTION POSTED AT 18/01/2020 - 07:23 AM

### A ride on the roller coaster costs 4 tickets while the boat ride only costs 3 tickets. Michael went on the two rides a total of 10 times and spent a total of 37 tickets Which equation is true?

Let x be the number of times that Michael rode on the roller coaster and let y be the number of times that he rode on the boat, then: x + y = 10 [because he went on the two rides a total of 10 times], and 4x + 3y = 37 [because a ride on a roller coaster costs 4 tickets and the boat ride costs 3 tickets and he spent a total of 37 tickets] From the first equation, 4x + 4y = 40 subtracting the second equation from the third equation gives: y = 3, and from the first equation x = 10 - y = 10 - 3 = 7 Therefore, Michael rode on the roller coaster 7 times and on the boat 3 times.

ANSWERED AT 18/01/2020 - 07:23 AM

QUESTION POSTED AT 18/01/2020 - 07:23 AM

### Based on the graph below, what is the total number of solutions to the equation f(x) = g(x)? graph of function f of x equals negative 11 by 3 multiplied by x plus 11 by 3 and graph of function g of x equals x cubed plus 2 multiplied by x squared minus x minus 2 One Two Three Four

The total number of solutions is one

Step-by-step explanation:

we have  To solve the system of equations equate f(x) and g(x) The solution of the system of equations is the intersection points both graphs

Using a graphing tool

see the attached figure

The solution of x There is only one point of intersection both graphs

therefore

The total number of solutions is one

ANSWERED AT 18/01/2020 - 07:23 AM

QUESTION POSTED AT 18/01/2020 - 07:23 AM

### In the figure, the ratio of the perimeter of rectangle ABDE to the perimeter of triangle BCD is 2/3 1 3/2 2 . The area of polygon ABCDE is 18 22 24 28 square units.

It would b 2/3 and the other one 2/4

ANSWERED AT 18/01/2020 - 07:23 AM

QUESTION POSTED AT 18/01/2020 - 07:23 AM

### Which statement best describes the effect of replacing the function f(x) = 2x + 2 with the function g(x) = 2x − 3? A .the graph shifts 1 units left B. the graph shifts 5 units left C. the graph shifts 5 units right D. the graph shifts 1 units right

Your answer should move to the left. which takes out C and D. The only way i would say to do this is to find X first and then plug the number into g(x) to see how many units it shifts.

ANSWERED AT 18/01/2020 - 07:23 AM

QUESTION POSTED AT 18/01/2020 - 07:23 AM

### Travis traveled 354 miles in 6 hours. What is his unit rate of speed in miles per hour? _____ miles per hour

59 miles per hour

Step-by-step explanation:

Travis traveled 354 miles in 6 hours.

We have to calculate his unit rate of speed in miles per hour.  = 59 miles

Travis traveled 59 miles per hour

ANSWERED AT 18/01/2020 - 07:22 AM

QUESTION POSTED AT 18/01/2020 - 07:22 AM

### According to the Rational Roots Theorem, which statement about f(x) = 25x^7 – x^6 – 5x^4 + x – 49 is true? Any rational root of f(x) is a multiple of –49 divided by a multiple of 25. Any rational root of f(x) is a multiple of 25 divided by a multiple of –49. Any rational root of f(x) is a factor of –49 divided by a factor of 25. Any rational root of f(x) is a factor of 25 divided by a factor of –49.

Any rational root of f(x) is a factor of -49 divided by a factor of 25.

Step-by-step explanation:

The Rational Root Theorems states that :

If the polynomial has any rational roots, then they must be in the form of Consider the polynomial in this case, we have and Any Rational root of f(x) is a factor of divided by a factor of ANSWERED AT 18/01/2020 - 07:18 AM

QUESTION POSTED AT 18/01/2020 - 07:18 AM

### The physical education teacher marked off a triangular section of the gym to play a game. Two of the triangle's sides were 7 feet and 9 feet respectively. If the perimeter of the triangle is 22 feet, what is the measure of the triangle's third side?

22 - (7 + 9) = 6 feet

ANSWERED AT 18/01/2020 - 07:18 AM

QUESTION POSTED AT 18/01/2020 - 07:18 AM

### Find the perimeter of a rectangular swimming pool that measures 12 feet by 22 feet.

The perimeter is 78ft. You do 12 times 2 plus 22 time 2 because a rectangle has 2 sets of equal sides.

ANSWERED AT 18/01/2020 - 07:18 AM

QUESTION POSTED AT 18/01/2020 - 07:18 AM

### What value of a makes the equation true 18/60=12/a a 30 b 4 c 20 d 40

by applying the cross product

ANSWERED AT 18/01/2020 - 07:16 AM

QUESTION POSTED AT 18/01/2020 - 07:16 AM

### Summer looked at the formula for the Pythagorean Theorem, a2 + b2 = c2, she said that it didn’t matter which sides of a right triangle were a, b, and c. Is she correct?

She is not correct because mixing the legs won't affect but mixing them with the hypotenuse would affect a lot.

ANSWERED AT 18/01/2020 - 07:16 AM

QUESTION POSTED AT 18/01/2020 - 07:16 AM

### Find the length of the unlabeled leg of the right triangle if the hypotenuse is 13 amd bottom leg is 12

Ok so
for a right triangle with legs legnth a and b, and hypotnuse legnth c
a^2+b^2=c^2

hypotonuse is 13
one leg is 12
other leg is ?
a=12
b=?
c=13

sub and find ?
12^2+?^2=13^2
144+?^2=169
minus 169 both sides
?^2=25
sqrt bot sies
?=5

the legnth is 5 units

ANSWERED AT 18/01/2020 - 07:15 AM

QUESTION POSTED AT 18/01/2020 - 07:15 AM

### What is the value of the dependent variable if the value of the independent variable is –4?f(x)= -3x^2 + 5x A. 28 B. –44 C. –68 D. 4

If you would like to know the value of the dependent variable if the value of the independent variable is - 4, you can calculate this using the following steps:

independent variable ... - 4 ... x
dependent variable ... f(x)

f(x)= -3x^2 + 5x
f(-4) = -3 * (-4)^2 + 5 * (-4) = -3 * 16 - 20 = -48 - 20 = - 68

The correct result would be C. –68.

ANSWERED AT 18/01/2020 - 07:15 AM

QUESTION POSTED AT 18/01/2020 - 07:15 AM

### The fraction 26/5 is between which two numbers? 2 and 3 3 and 4 4 and 5 5 and 6

5 and 6

Step-by-step explanation:

We need to find that between what two numbers the fraction lies.

In order to know from the given choices between what two numbers lies, we first need to find the decimal value of .

We know that Now, let us consider given choices one by one.

Clearly, 5.2 is greater than 3, it cannot lie between 2 and 3.

Clearly, 5.2 is greater than 4, it cannot lie between 3 and 4.

Also, 5.2 is greater than 5, it cannot lie between 4 and 5.

Now, 5.2 is greater than 5 and less than 6. So, we can say that 5.2 or lies between 5 and 6.

Hence, lies between 5 and 6.

So, choice number (4) is correct.

ANSWERED AT 18/01/2020 - 07:15 AM

QUESTION POSTED AT 18/01/2020 - 07:15 AM

### Find the quotient of -16 and 4. -64 64 -4 4

The answer is -4 hope this helps

ANSWERED AT 18/01/2020 - 07:15 AM

QUESTION POSTED AT 18/01/2020 - 07:15 AM

### What is the resulting equation when the expression for y in the second equation is substituted into the first equation? 3x + y = 1 y = 6 - 4x a. -x + 6 = 1 b. x + 6 = 1 c. 7x + 6 = 1

When expression for y in the second equation is substituted into the first equation than the resulting equation -x + 6 = 1 .

Option (a) is correct .

Step-by-step explanation:

As given the equations in the questions are

3x + y = 1

y = 6 - 4x

As expression for y in the second equation is substituted into the first equation .

i.e put y = 6 - 4x in 3x + y = 1  .

3x + 6 - 4x = 1

Solving the above

-x + 6 = 1

Therefore the when expression for y in the second equation is substituted into the first equation than the resulting equation -x + 6 = 1 .

Option (a) is correct .

ANSWERED AT 18/01/2020 - 07:14 AM

QUESTION POSTED AT 18/01/2020 - 07:14 AM

### Which equation can be used to find the perimeter of a regular octagon with sides of length 12 m? A. P = 8 + 12 B. P = 8(12) C. P = 12 ÷ 8 D. P = 2(8) + 2(12)

The basic definition of a perimeter is the boundary line of an object. For shapes and figures, this is basically the sum of the outermost sides that define the object. Since an octagon has eight sides, with each side measuring 12m, the perimeter can be obtained by multiplying 12 m by 8 sides, or in equation form:

P = 8(12)

Among the choices, this is letter B.

ANSWERED AT 18/01/2020 - 07:14 AM

QUESTION POSTED AT 18/01/2020 - 07:14 AM